The Effect of Profitability (ROA) and Free Cash Flow on Dividend Payout Ratio in Manufacturing Companies Listed on the IDX in 2019-2022 - Nasrulloh, Nasrulloh; Supraptiningsih, Joelianti Dwi; Alvianingsih, Vivi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This study aims to analyze the effect of profitability (ROA) and free cash flow on the dividend payout ratio in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. Data was collected from manufacturing companies using quantitative methods and analyzed using multiple regression with the help of the SPSS program. The findings of this study indicate that profitability and free cash flow have a significant influence on the dividend payout ratio. This indicates that the financial performance of manufacturing companies has an impact on dividend payout policy. In addition, this study also reveals that manufacturing companies that are able to manage their assets effectively and efficiently tend to have good financial performance, which allows them to pay cash dividends. The results of this study provide new insights into understanding the relationship between financial factors and the dividend policy of manufacturing companies. The implications of these findings can be an important consideration in making investment decisions in the stock market, as well as contributing to understanding the financial dynamics of manufacturing companies on the IDX.